Peningkatan Kadar Zn Beras Pecah-Kulit pada Sistem Penggenangan Berselang Melalui Aplikasi Pupuk Kandang Diperkaya Zn Heptahidrat - Salawati Salawati; Sjarifuddin Ende; Mohammad Basir; Indrianto Kadekoh; Abdul Rahim Thaha (Institut Pertanian Bogor, 2021)
Zn levels in rice are essential for maintaining consumer health. However, Zn deficient plants can reduce levels of Zn in grains and the ability of plants to express their genetic potentials. This study examines the use of cow manure enriched with Zn heptahydrate on increasing Zn levels of broken skin rice. The experiment was arranged in a randomized single factor group design with seven levels of manure dose treatment, namely: 0; 2.5; 5, 7.5, 10, 12.5, 15 tons ha-1, with 3 replications. Spacing was 30 cm x 30 cm with a size of 3 m x 4 m. The parameters observed were plant growth, the weight of 1,000-grain, percentage of empty grain, production, Zn and protein contents of the brown rice. The collected data were analyzed using analysis of variance with a confidence interval of 5%, followed by the Duncan test of 5%. The results showed that the application of cow manure with a dose of 10 tons ha-1 enriched by 5 kg ha-1 Zn heptahydrate could increase the number of productive tillers, weight of 1,000-grains, production, Zn and protein contents of the brown rice as well as suppress the grainy rice grain of Mekongga variety of lowland rice on the intermittent flooding. Keywords: brownrice, cow manure, irrigation system, Zn heptahydrate